2021
DOI: 10.1111/1759-7714.14245
|View full text |Cite
|
Sign up to set email alerts
|

Icaritin alleviates docetaxel‐induced skin injury by suppressing reactive oxygen species via estrogen receptors

Abstract: Background: Docetaxel (DTX) exhibits antitumor effects against breast cancer by stabilizing microtubules and increasing the accumulation of reactive oxygen species (ROS). DTX extravasation during infusion often causes skin injury. The present study aimed to investigate the effects and mechanisms of icaritin (ICT) on DTX-induced skin injury. Methods: The effects of ICT on the viability and apoptosis of HaCaT cells were measured by SRB assay and flow cytometry, respectively. Endogenous LC3 puncta and microtubule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In addition, icaritin can target MyD88 and IkBα to inhibit IL-6/JAK/STAT3 signaling, thereby regulating the TME and inhibiting tumor cell growth [554][555][556]. Further, a study reported resensitization of cancer cells to medicinal agents by icaritin, as well as the attenuation of side effects indicating the potential for clinical co-treatment including icaritin as a supplementary drug [557]. Further evaluation of icaritin for application in regulation of hematopoiesis and hematological cancer therapy is warranted, owing to its apoptotic properties and immunomodulatory effects.…”
Section: Icaritinmentioning
confidence: 99%
“…In addition, icaritin can target MyD88 and IkBα to inhibit IL-6/JAK/STAT3 signaling, thereby regulating the TME and inhibiting tumor cell growth [554][555][556]. Further, a study reported resensitization of cancer cells to medicinal agents by icaritin, as well as the attenuation of side effects indicating the potential for clinical co-treatment including icaritin as a supplementary drug [557]. Further evaluation of icaritin for application in regulation of hematopoiesis and hematological cancer therapy is warranted, owing to its apoptotic properties and immunomodulatory effects.…”
Section: Icaritinmentioning
confidence: 99%
“…This study also showed that this biomaterial inhibits gastric cancerous cell invasion and cell migration and is the main process for suppressing the expression of genes associated with Rac1 and VASP cell motility ( Figure 4 ) [ 142 ]. The results of these works showed that ICRN and its derivatives prevent cancer cell metastasis by regulating proteins that are critical for cancer metastasis [ 143 , 144 ]. A study by Song et al found that ICRN could inhibit the pulmonary metastasis pattern of 4T1 cells in BALB/c mice.…”
Section: Cancer Therapy By Icrnmentioning
confidence: 99%
“…Flavonoids are an important class of small-molecule natural phenolic phytochemicals with various health protective properties and few apparent side effects. Icaritin (ICT, 1 ) is a prenylated flavonoid and is a main constituent in plants of the Epimedium genus. , Previous studies have shown that ICT exhibits a variety of pharmacological activities, such as antitumor, anti-inflammatory, and neuroprotective activities. ICT, which shows particularly outstanding anti-HCC activity, has been developed and approved by the National Medical Products Administration of the People’s Republic of China as a new drug for the treatment of advanced HCC . However, ICT still exhibits some drawbacks that limit its potency, such as poor water solubility, low bioavailability, and low oral absorption. , Performing further optimization to improve the pharmacological properties of ICT and designing novel ICT analogues with more potent anti-HCC activity is a worthwhile objective.…”
mentioning
confidence: 99%